2013
DOI: 10.3892/mmr.2013.1512
|View full text |Cite
|
Sign up to set email alerts
|

Oxymatrine ameliorates non-alcoholic fatty liver disease in rats through peroxisome proliferator-activated receptor-α activation

Abstract: Non-alcoholic fatty liver disease (NAFLD) is the most common type of liver disease worldwide. Recent studies have reported that oxymatrine (OMT), an active monomer isolated from Sophora flavescens Ait. (kushen), ameliorates NAFLD in rats. In order to explore the possible molecular mechanism involved, we used an NAFLD rat model with hyperlipidemia, which had been established by feeding a high‑fructose diet (HFD) for eight weeks, and the model rats were subsequently treated with OMT (80 mg/kg/day) for a further … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 27 publications
2
16
1
Order By: Relevance
“…Several preclinical studies have evaluated its beneficial effects and investigated the underlying mechanism. Shi et al [17], [18] showed that oxymatrine simultaneously down-regulated sterol regulatory element binding transcription factor 1 and up-regulated peroxisome proliferator activated receptor alpha mediated metabolic pathways to attenuate hepatic steatosis in rats with non-alcoholic fatty liver disease. It has been reported that oxymatrine protected animals against ischemia and reperfusion-induced liver, heart, and intestinal injuries involving extracellular signal regulated kinase, c-Jun N-terminal kinase, and p38 mitogen-activated protein kinases signaling pathways [19][21].…”
Section: Introductionmentioning
confidence: 99%
“…Several preclinical studies have evaluated its beneficial effects and investigated the underlying mechanism. Shi et al [17], [18] showed that oxymatrine simultaneously down-regulated sterol regulatory element binding transcription factor 1 and up-regulated peroxisome proliferator activated receptor alpha mediated metabolic pathways to attenuate hepatic steatosis in rats with non-alcoholic fatty liver disease. It has been reported that oxymatrine protected animals against ischemia and reperfusion-induced liver, heart, and intestinal injuries involving extracellular signal regulated kinase, c-Jun N-terminal kinase, and p38 mitogen-activated protein kinases signaling pathways [19][21].…”
Section: Introductionmentioning
confidence: 99%
“…and increase the level of IL‐10 in patients with chronic HBV infection, which might be one of the mechanisms of action in reversing liver fibrosis . The satisfactory efficacy/toxicity profile of oxymatrine, together with its economic viability, make it a good candidate for the management of complex diseases …”
mentioning
confidence: 99%
“…LXRα can bind the retinoid X receptor (RXR), thereby activating the transcription of downstream genes [7]. In the liver, LXRα is found to activate SREBP-1 gene transcription, which then enhances the subsequent activation of lipogenic genes, including fatty acid synthase (FAS), acetyl-CoA carboxylase (ACC1), and stearoyl-coenzyme A desaturase (SCD-1) [8].…”
Section: Introductionmentioning
confidence: 99%